Strategi Komunikasi Digital Marketing Untuk Meningkatkan Daya Beli Konsumen Disaat Pandemi Covid-19 - Roosita Cindrakasih (Prisani Cendekia Institute, 2022)
This research focuses on digital marketing communication strategies in Vida Bekasi housing. With the aim of this study to find marketing communication strategies through effective digital marketing to increase people's purchasing power during the covid-19 pandemic and support consumer decisions in choosing the Vida Bekasi area. With Marketing Mix Theory (4P). The object of this research is the Digital Marketing Communication Strategy created by the Sales team and the Vida Bekasi Digital Marketing team. This research uses a qualitative method with a case study approach. With a descriptive analysis that includes observation, interviews, documentation studies and data analysis. With three lines of data analysis, namely data reduction, data presentation, and drawing conclusions. While the validity of the data used are data triangulation, theory triangulation, and methodological technique triangulation. The results of this study show that the products from Vida Bekasi are different from property developer products in general. In addition, there is a choice of residential forms, the prices offered also vary, Marketing Promos, residential concepts, and digital marketing strategies are also one of the attractions for consumers to keep buying during the Covid-19 pandemic